Trehalose biosynthesis is involved in sporulation of Stagonospora nodorum - Lowe, R.; Lord, M.; Rybak, K.; Trengove, R.; Oliver, Richard; Solomon, P. (Academic Press, 2009)
Stagonospora nodorum is a necrotrophic fungal pathogen that is the causal agent of leaf and glume blotch on wheat. S. nodorum is a polycyclic pathogen, whereby rain-splashed pycnidiospores attach to and colonise wheat tissue and subsequently sporulate again within 2–3 weeks. As several cycles of infection are needed for a damaging infection, asexual sporulation is a critical phase of its infection cycle. A non-targeted metabolomics screen for sporulation-associated metabolites identified that trehalose accumulated significantly in concert with asexual sporulation both in vitro and in planta. A reverse-genetics approach was used to investigate the role of trehalose in asexual sporulation. Trehalose biosynthesis was disrupted by deletion of the gene Tps1, encoding a trehalose 6-phosphate synthase, resulting in almost total loss of trehalose during in vitro growth and in planta. In addition, lesion development and pycnidia formation were also significantly reduced in tps1 mutants. Reintroduction of the Tps1 gene restored trehalose biosynthesis, pathogenicity and sporulation to wild-type levels. Microscopic examination of tps1 infected wheat leaves showed that pycnidial formation often halted at an early stage of development.Further examination of the tps1 phenotype revealed that tps1 pycnidiospores exhibited a reduced germination rate while under heat stress, and tps1 mutants had a reduced growth rate while under oxidative stress. This study confirms a link between trehalose biosynthesis and pathogen fitness in S.nodorum.